Risk of Dis-lipids Syndrome in Modern Society - Udristioiu, Aurelian; Cojocaru, Manole (International Journal For Research In Health Sciences And Nursing, 2016)
Aim of this work was to emphasis the preclinical evaluation of dis-lipids syndromes types at the patients which were presented to a routine control for checking health status, in the hospital ambulatory.Material and Method: Were analyzed 60 patients, registered in Clinical Laboratory, assessing by running on the Hitachi 912 Analyzer, the principal biochemical parameters of lipid metabolism: Cholesterol, Triglycerides and fractions of Cholesterol, HDL and LDL. From the total of 60 patients 35 were females and 25 males. Results The persons with an alarm signal of atherosclerotic process were in 28 % and persons with low HDL was in 17%. The cases with atherosclerotic index, report-LDL/HDL>3.5 for men and 2.5 for women were in 14 % , the cases with predictive value with coronary risk, reportCO/HDL>5 were presented in 5 % and the cases with dis-lipid syndrome type 2- 4, with high Cholesterol and Triglycerides, were presented in 30% percent. Conclusions Lipids controls, and its fractions, are necessary to be prevented atherosclerotic process in the incipient status of ill.